A Comparative Study of Proficiency in English Language of Male and Female Secondary School Students - A. Kumar; Negi, Monika (JOURNAL OF INDIAN EDUCATION, 2021)
English was only a library language in the past but it is now viewed as the language of opportunity of acquiring jobs, quest for global identity, and thus prompts efforts of all state government to make the language accessible to all. This has become an important language in our country and is widely used in media, personal life, courts of law and administration. Therefore, it is necessary that students are taught English in proper ways so that they can gain command over it. In spite of immense importance and globalised acceptance of necessity of knowledge of English Language, the average Indian student is not able to either learn English or communicate in English with a reasonable level of proficiency in has become significant. The purpose of this study is to analyse the English Language Proficiency of the male and female students studying at secondary level. The sample consisted of 154 students studying at the secondary level. The tool used for data collection was English Language Proficiency Test developed by K.S. Mishra and Ruchi Dubey. The result of the study revealed that there is no significant difference between the English Language Proficiency of the male and female students studying at the secondary level.